CFD study and experimental validation of low liquid-loading flow assurance in oil and gas transport: studying the effect of fluid properties and operating conditions on flow variables. Issue 12 (December 2020) - Ballesteros Martínez, Miguel; Pereyra, Eduardo; Ratkovich, Nicolás
Abstract: Low liquid-loading flow frequently occurs during the transport of gas products in various industries, such as in the Oil & Gas, the Food, and the Pharmaceutical Industries. Even small amounts of liquid can have a significant effect on the flow conditions inside the pipeline, such as increased pressure loss, pipe wall stresses and corrosion, and liquid holdup along the pipeline. However, most studies that analyze this type of flow only use atmospheric pressures and horizontal 1-in or 2-in pipes, which do not accurately represent the range of operating conditions present in industrial applications. Therefore, this study focused on modeling low liquid-loading flow in medium-sized (6–10 in) pipes, using CFD simulations and experimental data from the University of Tulsa, and then applying it to real operating conditions from a Colombian gas pipeline. An acceptable difference was observed between experimental and CFD data, both for the liquid holdup (18%) and for the pressure drop (12%). Variables like pressure drop and wall shear stress increase with phase velocity, operating pressure, and pipe inclination. Liquid holdup increases with liquid velocity but decreases with all other factors. The relation of flow variables with phase velocities is of particular interest: Doubling the gas velocity decreased holdup 70% and increased pressure drop tenfold. On the other hand, the presence of the liquid phase seems to be more influential on process variables than its exact flowrate; the introduction of the liquid phase to a single-phase gas causes an increase in pressure loss by a factor of three, but doubling the liquid velocity only increases the pressure loss by a further 30%. Abstract : Chemical engineering; Petroleum engineering; Transport process; Computational fluid dynamics; Petroleum industry; Natural gas; CFD; Low liquid-loading flow; Pipeline transport; Pressure drop; Flow assurance.